Penerapan Algoritma Blok Cipher Oe-Ck (Odd-Even Confusing Key) Pada Aplikasi Pengamanan Gambar - Lasma Hutagaol (AMIK STIEKOM SUMATERA UTARA, 2023)
In cryptography, encryption and decryption, encryption is the process of securing the original image data into an incomprehensible image, while decryption is the process of returning encrypted image data so that it is easy to read. In the process of encryption and decryption there is a key which functions as a bridge between encryption and decryption in supporting the strength of image security. Based on these problems the author will make a process of securing images in the form of images that can be carried out in encrypting images into certain algorithm forms. This is possible considering that an image can be represented in a table containing binary numbers. In this study the OE-CK block cipher algorithm will be implemented to encode images in jpeg format, which has a size of 1000x1200 pixels. The key used to encode the image uses the key